The Right Way Draw People : Including Cartoons & Caricatures - Linley, Mark (Kingswood Right Way)
Whether your ambition is to make it big as a professional portrait artist, funny cartoonist or clever caricaturist, or simply to improve your figure drawing skills for work or pleasure, this book should have you churning out first-rate sketches in no time at all.
Including Illustration
Keywords: Portrait drawing--Technique -- Human figure in art -- Figure drawing--Technique